Efeito da fototerapia com laser de baixa potência no remodelamento dos colágenos I e III no processo de regeneração do músculo esquelético de rato - Souza, Thais Oricchio Fedri de (2009)
Laser phototherapy (LPT) has been employed to stimulate repair in different tissues. However, its role in muscle remodeling is not yet well clarified, especially its effect on the collagen component of the extracellular matrix. The aim of the present study was to investigate the effect of laser on the remodeling of collagens type I and III during skeletal muscle regeneration following cryoinjury. Fifty Wistar rats were divided into four groups: control, sham, cryoinjury and laser-treated cryoinjury. The laser-treated group underwent three weekly sessions of InGaAlP (660nm) punctual laser irradiation with 20 mW,0.04 cm2 focal spot, 5 J/cm2 for 10 seconds with 200mJ of total energy dose . Five animals were sacrificed on Days 1, 7, 14 and 21 after the injury. The muscles were processed and submitted to hematoxylin/eosin and imunohistochemical staining. The histological slices were analyzed qualitatively, semi-quantitatively and quantitatively. The data were submitted to statistical analysis using the Kruskal-Wallis test. The morphological and semi-quantitative findings of edema, inflammatory process, myonecrosis and presence of new immature fibers revealed that the cryoinjury group and the laser-treated cryoinjury group exhibited a similar muscle repair pattern. However, the analysis of the distribution of collagen I and III revealed a significant increase in the depositing of these proteins in the laser-treated group when compared to the control. The laser-treated group also exhibited an increase in both collagen types at seven days in comparison to the cryoinjury group. In conclusion, laser therapy promoted a change in the depositing of collagen types I and III during the muscle repair process in rats following cryoinjury.